Finanzanalysen beim Internationalen Eisenbahnverband (UIC). - Sterba, Roman; Pastor, Otto (Deutscher Verkehrs-Verl., 2008)
Jedes Bahnunternehmen benötigt aussagefähige Daten, die seinen Führungen helfen sollen, die festgelegten Ziele zu verfolgen, die richtigen Entscheidungen zu fällen und für die Zukunft Verbesserungen anzusteuern. Informationen dazu können Kennzahlen liefern. Mit Indikatoren kann sich ein Bahnunternehmen an anderen messen. Das Komitee Wirtschaft, Finanzen und Umwelt des Internationalen Eisenbahnverbands (UIC) hat in seiner Sitzung Ende 2000 beschlossen, Maßnahmen und Methoden zusammentragen zu lassen, die sich bei den Mitgliedsbahnen zur Produktivitätsverbesserung und Effizienzsteigerung des Bahnsystems bewährt haben. Mit der Durchführung dieser Untersuchungen wurde die UIC-Arbeitsgruppe Benchmarking beauftragt.

The article describes the systematic finance analysis at UIC, which ensure extensive information on productivity and effectiveness of European railway sector. The working group Financial Indicators is for annual survey on financial situation of member companies and following assessment and evaluation of figures at UIC responsible. All figures flow from relevant annual reports structured under the sectoral EU's regulations and directives, the first railway package especially. Attention is paid to the keeping of accounts and publication of figures separately for both, passenger and freight transport, infrastructure and other activities. Furthermore, public funds paid to one of these activities may not be transferred to the other. The railways execute the measurement of their effectiveness and productivity with a view to follow the results that have been achieved by the best enterprise.
Benchmarking at UIC.
Keywords: Verkehr; Verkehrsunternehmen; Eisenbahn; Schienenverkehr; Produktivität; Indikator; Investition; Ertrag; Verschuldung; Verkehrswirtschaft; Finanzanalyse; Personalplanung; Verkehrsmarkt; Verkehrsleistung; Benchmarking; Kennzahl; Wertschöpfung; Verkehrsforschung